Characterization of Snack Food Bars Made of Nixtamalized Corn Flour and Flour Of Nike Fish for Emergency Food - Rahmiyati Kasim; Lisna Ahmad; Suryani Une; Yoyanda Bait; Siti A. Liputo (Hasanuddin University, 2017)
Utilization of local food source such as nixtamalized corn flour and nike flour as base ingredients in producing snack bars may add the product value and also reduce production costs. The purpose of this study was to produce a prototype snack food bars weighing 50 grams for each bar, containing calories that meet the standards of Emergency Food Product (EFP) by 233 kcal/bar, and being favored by consumers. Snack food bars produced in this study used the formulation in the previous study, consisted of 26.77% nixtamalized corn flours, 6.69% nike flours, 9.37% corn starch, 20.08% chocolate, 13.01% margarine, 13.38% egg whites, and 13.38% sugar. Snack food bars were produced through six steps: weighing ingredients, mixing, molding, baking in the oven, cooling, and packaging. The baking process used three combinations of temperature and time, each with 3 replicates. Bars were baked at 1000C for 20 minutes, and then followed by temperature of 1400C (treatment A), 1500 C (treatment B), or 1600C (treatment C) for 40 minutes. Snack food bars produced by baking temperature combination were less preferred by the panelists based on the taste attributes due to the distinctive flavor of nike flours persisted in the bars. Baking temperature C (at 1000 C for 20 minutes, followed by 1600C for 40 minutes) got the highest score based on the texture attributes. The nutrient and calorie content of snack food bars produced did not show much difference with the formulation result. Snack food bars produced in this study contained 10.1751 g fat, 3.5694 g protein and 32.2681 g carbohydrate in every 50 g of snack bars. Based on the formulation result, snack food bars contained 9.8 g fat, 5.84 g protein, and 30.37 g carbohydrate per 50 g of snack bars. Snack food bars produced in this study contained 234.926 kcal per 50 g of snack bar while based on the formulation result, snack food bars contained 233 kcal per 50 g of snack bar. This implies that Snack food bars based local product has the potential to developed in the regional in security food in the face of emergency condition.